ENHANCING ENGLISH VOCABULARY MASTERY IN YOUNG LEARNERS THROUGH WHISPERING GAMES (Yavana Bhasha : Journal of English Language Education, 2026)
The study aimed to improve students’ vocabulary mastery through the use of the Whispering Game. A two-cycle classroom action research was applied in conducting this study, involving twenty-two (22) 4th-grade students of a public elementary school in Denpasar, Bali. In the process of collecting the data, the researcher administered pre-tests and post-tests to determine the improvement in students’ vocabulary mastery before and after the intervention. A questionnaire was also administered to explore students' responses throughout the teaching and learning process. The results of this study indicate that the Whispering Game significantly improved students’ vocabulary mastery, as evidenced by the increase in the class mean score from 55 in the pre-cycle to 85 in the second cycle. This improvement was further supported by questionnaire data, which revealed highly positive student responses toward the Whispering Game.